2019
DOI: 10.3390/ma12172654
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Autogenous Shrinkage in High-Strength Mortars with Saturated Tea Waste Particles

Abstract: The purpose of this study was to prevent early age autogenous shrinkage in high-strength mortars with saturated tea waste particles. In general, high strength and high performance concretes are made with low water/binder ratios; hence, they are susceptible to shrink at early ages. This shrinkage occurs due to self-desiccation that leads to autogenous shrinkage. To overcome self-desiccation problems in high-strength cement composites, it is necessary to keep the composites moist for a long time. Pre-saturated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…From the results obtained, it can be seen that the workability increased by 16% and 10% at higher percentages of replacement of 3% and 4%, respectively. These results are consistent with those of previous studies in which a decrease in slump was demonstrated (Jakhrani et al 2019;Fang et al 2022). According to (Fang et al 2022) the primary results of previous studies showed that the workability of mortar containing tea waste as a cement substitute was increased due to the high neness of tea waste and the treatment process for tea waste before use compared to owing mortar without tea waste.…”
Section: Resultssupporting
confidence: 94%
“…From the results obtained, it can be seen that the workability increased by 16% and 10% at higher percentages of replacement of 3% and 4%, respectively. These results are consistent with those of previous studies in which a decrease in slump was demonstrated (Jakhrani et al 2019;Fang et al 2022). According to (Fang et al 2022) the primary results of previous studies showed that the workability of mortar containing tea waste as a cement substitute was increased due to the high neness of tea waste and the treatment process for tea waste before use compared to owing mortar without tea waste.…”
Section: Resultssupporting
confidence: 94%